2015
DOI: 10.2147/opto.s63484
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of meibomian gland dysfunction: optometrists' perspective

Abstract: Meibomian gland dysfunction (MGD) is commonly encountered among eye care professionals. Our understanding of the pathophysiology for the development of MGD has greatly expanded in recent years, which helped increase awareness of the disease. Despite increased awareness, it is essential for eye care professionals to make a conscious effort to properly examine the meibomian glands through gland expression even for asymptomatic patients. At minimum, early management should include patient education and supportive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 80 publications
0
19
0
2
Order By: Relevance
“…Lastly, MGD has been defined by subcommittee of The International Workshop on MGD (IWMGD) in 2011 as ''a chronic, diffuse abnormality of the MGs, commonly characterized by terminal duct obstruction and/or qualitative/quantitative changes in the glandular secretion which may result in alteration of the tear film, clinical apparent inflammation, OSD and symptoms of eye irritation''. [2][3][4]…”
Section: Definitionmentioning
confidence: 99%
See 3 more Smart Citations
“…Lastly, MGD has been defined by subcommittee of The International Workshop on MGD (IWMGD) in 2011 as ''a chronic, diffuse abnormality of the MGs, commonly characterized by terminal duct obstruction and/or qualitative/quantitative changes in the glandular secretion which may result in alteration of the tear film, clinical apparent inflammation, OSD and symptoms of eye irritation''. [2][3][4]…”
Section: Definitionmentioning
confidence: 99%
“…The functions of Meibomian lipids include providing a smooth optical surface for the cornea, reduction evaporation of the tear film during waking hours, lubrication during blinking, decreasing the surface tension, enhancing the stability and the spreading of the tear film, forming a barrier to prevent bacteria from entering the tear film, prevention of spillover of tears from the lid margin and the contamination of the tear film by sebum and sealing the opposing lid margins during sleep. [2][3][4][5][6][7][8][9] MGD is one of the most common diseases of MGs. However, it is often overlooked clinically.…”
Section: The Importance Of the Functions Of Mgsmentioning
confidence: 99%
See 2 more Smart Citations
“…Opitz et al suggested that if older patients were identified and treated before they became symptomatic, end-stage disease or MG atrophy may not occur [17]. Summerton suggested that Omega-3 dietary supplementation for blepharitis and MGD may decrease the red blood cell and plasma ratios of omega-6 to omega-3 and improve the overall ocular surface index score, TBUT and meibum score [18].…”
Section: Original Research Articlementioning
confidence: 99%